Anti-pyretic activity of two varieties of Hibiscus Rosa Sinensis L. - Abdul Aziz, Muhammad Wahizul Haswan; Raduan, Siti Zaleha; Abd Hamid @ Abdul Razak, Roslida; Zakaria, Zainul Amiruddin; A., Zuraini; Abdullah, Muhammad Nazrul Hakim (Oriental Scientific Publishing, 2021)
Hibiscus rosa-sinensis has been traditionally used by local communities to treat fever. However, there are only limited data have been published to support the antipyretic effects. The objective of this study is to investigate the antipyretic properties and possible mechanism of the ethanol extracts of Hibiscus rosa-sinensisL. (red colored flower) and Hibiscus rosa-sinensisvar. Alba (white colored flower). Phytochemical analysis, heavy metals screening and acute toxicity test were done to evaluate the safety of extracts. The first model ran induced fever in rats by injecting Brewer's Yeast subcutaneously and then treated with 4 extracts at dosage 5 & 50 mg/kg. The dosages used for the study were obtained by the acute toxicity test. Ibuprofen was used as a reference drug, with dose 100 mg/kg. Temperatures of rats were measured using a digital thermometer. The results were expressed as mean ± S.E.M. and analyzed using the SAS system. The results of the study showed that white flower extract 5mg/kg and 50 mg/kg significantly (p <0.05) reduced the total temperature when compared to positive control group. Therefore, this research suggests the probability for its therapeutic effectiveness as plant-based antipyretic agent as claimed by traditional medicine practitioners.